International Protection of Intellectual Property - Gene M. Grossman; Edwin L.-C. Lai (Center for Economic Studies and ifo Institute (CESifo), 2002)
We study the incentives that governments have to protect intellectual property in a trading world economy. We consider a world economy with ongoing innovation in two countries that differ in market size and in their capacities for innovation. We associate the strength of IPR protection with the duration of a country's patents that are applied with national treatment. After describing the determination of national policies in a non-cooperative regime of patent protection, we ask, Why are patents longer in the North? We also study international patent agreements by deriving the properties of an efficient global regime of patent protection and asking whether harmonization of patent policies is necessary or sufficient for global efficiency.
Keywords: 330; patents; intellectual property; harmonization; TRIPs.